Asymmetries in speech errors and their implications for underspecification - Pouplier, Marianne; Goldstein, Louis (ZAS Papers in Linguistics, 2002)
This paper follows a new perspective on speech errors within the framework of Articulatory Phonology, as proposed by Goldstein et al. (in prep.). On the basis of kinematic evidence, their work has demonstrated that speech errors are not restricted to categorical exchanges of position of segmental units, but rather gestures that compose segments can exhibit errors that vary from zero to maximal in magnitude. Here we report results from two perceptual experiments which use stimuli selected on the basis of their articulatory properties only, covering a range of errorful gestural activations. The outcome of the perceptual experiments suggests that different segments show different degrees of vulnerability to (subsegmental) speech errors: While listeners detected errors reliably for some segments, for other segments the reaction to errorful and non-errorful tokens was not distinct. The data suggest that at least for some error types an asymmetric error distribution arises due to perception, while production itself is not asymmetric. However, for error types involving segments whose gestural compositions stand in a subset relationship to each other (as described below), asymmetries may indeed originate in production due to the overall dominance of a gestural intrusion bias observed in the production data of Goldstein et al. (in prep.).